DDR1 and DDR2 physical interaction leads to signaling interconnection but with possible distinct functions. Issue 4 (4th July 2018) - Croissant, Coralie; Tuariihionoa, Adjanie; Bacou, Marion; Souleyreau, Wilfried; Sala, Margaux; Henriet, Elodie; Bikfalvi, Andreas; Saltel, Frederic; Auguste, Patrick
ABSTRACT: Discoidin domain receptors 1 and 2 (DDR1 and DDR2) are members of the tyrosine kinase receptors activated after binding with collagen. DDRs are implicated in numerous physiological and pathological functions such as proliferation, adhesion and migration. Little is known about the expression of the two receptors in normal and cancer cells and most of studies focus only on one receptor. Western blot analysis of DDR1 and DDR2 expression in different tumor cell lines shows an absence of high co-expression of the two receptors suggesting a deleterious effect of their presence at high amount. To study the consequences of high DDR1 and DDR2 co-expression in cells, we over-express the two receptors in HEK 293T cells and compare biological effects to HEK cells over-expressing DDR1 or DDR2. To distinguish between the intracellular dependent and independent activities of the two receptors we over-express an intracellular truncated dominant-negative DDR1 or DDR2 protein (DDR1DN and DDR2DN). No major differences of Erk or Jak2 activation are found after collagen I stimulation, nevertheless Erk activation is higher in cells co-expressing DDR1 and DDR2. DDR1 increases cell proliferation but co-expression of DDR1 and DDR2 is inhibitory. DDR1 but not DDR2 is implicated in cell adhesion to a collagen I matrix. DDR1, and DDR1 and DDR2 co-expression inhibit cell migration. Moreover a DDR1/DDR2 physical interaction is found by co-immunoprecipitation assays. Taken together, our results show a deleterious effect of high co-expression of DDR1 and DDR2 and a physical interaction between the two receptors.